FOCUS RESEARCH ON HALAL FOOD MARKETING - Fadli Agus Triansyah (Journal of Management and Islamic Finance, 2023)
Halal food is a category of food or beverage that Muslims may consume according to Islamic law. Halal cuisine must also adhere to strict standards of sanitation and hygiene, which makes it noted for its cleanliness and higher quality. This study utilised a systematic review on halal food marketing scopus database from 2021-2023. In this research, the keyword used is "Halal Food Marketing" in the Scopus database. After conducting the screening, the researchers found 11 articles that met the predetermined criteria. Several research focuses on halal food marketing, namely intention to purchase, halal cosmetics, millennials, religiosity, halal food consumption, Halal brand image, Halal brand satisfaction, Halal brand trust, Halal brand equity, Customer attitude, Product attributes, Marketing stimuli, Halal food , Halal Tourism, halal, marketing, perceived risk, value, trust, purchase intention, product, Halal market, Islamic hospitality, Muslim traveler, Muslim-minority country, Halal hotel, Halal-friendly hotel, Islamic hotel branding, Relational value, utility value, Halal brand resonance, Halal brand relationship quality, supply chain integration, demand for halal products, halal marketing, process quality improvement, food safety concerns, health consciousness on sustainable product performance, Halal foods, Performance, Drivers, and Key success factors. Through proper marketing, halal food producers can increase consumer awareness about their products and expand their market.